ANALISIS KESESUAIAN LAHAN UNTUK KAWASAN PERMUKIMAN DI KECAMATAN DAU BERDASARKAN ARAHAN RTRW KABUPATEN MALANG TAHUN 2010-2030 - Kresnajaya, Amin; Taryana, Didik (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Dau Sub-district is one of the sub-districts in Malang Regency that functions as a settlement development due to the urban development orientation of Malang City. This research aimed to assess the suitability of settlement land in existing conditions and based on the direction of the Malang District RTRW 2010-2030. This research was conducted using a GIS-based process with the AHP weighting method. The AHP parameters consisted of slope, rainfall, COLE index, land movement vulnerability, flood vulnerability, land use, and distance from roads. AHP processing was carried out using Expert Choice 11 software. The land suitability of Dau Sub-district settlements obtained results: S1 class covering 37,12%; S2 class 26,05%; S3 class 16,48%; N1 class 16,32%; and N2 class 4,03% of the study area. Land suitability for settlements in Dau Sub-district based on the 2010-2030 Malang Regency RTRW obtained results: S1 class covers 39,96%; S2 class 47,08%; S3 class 8,23%; N1 class 4,55%; and N2 class 0.18% of the research area. Referring to the RTRW map with existing conditions, the development of residential land has deviated by 39.25%. Areas with classes S1 and S2, which are suitable classes for the development of residential areas, dominate with an even distribution across all villages in Dau Sub-district. The main inhibiting factors affecting the suitability value are slope and disaster vulnerability.